2017
DOI: 10.18632/oncotarget.23267
|View full text |Cite
|
Sign up to set email alerts
|

Cryptotanshinone induces ROS-mediated apoptosis in human gastric cancer cells

Abstract: Cryptotanshinone (CT), isolated from the plant Salvia miltiorrhiza Bunge, has been reported to have potential anticancer effects on human prostate and breast cancer cells. However, the mechanisms of action of CT on gastric cancer (GC) cells are not well understood. Here we investigated the antitumor effects of CT on GC cells and its possible molecular mechanism. We found CT suppressed viability of twelve GC cell lines in a dose-dependent manner. CT induced cell cycle arrest at the G2/M phase and mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…However, other previous studies confirmed NAC inhibited anti-tumor effect of some chemical agents isolated from the plant, such as britannin, (33) Umbilicaria esculenta, (34) and cryptotanshinone. (35) Consistent with those previous studies, NAC also abolished quercetin-induced NUPR1-depended autophagic cell death in OS cells both in vitro and in vivo. These results also suggested that clinical trials will need to be performed to test if NAC combined with other antioxidants or metabolic modulators are effective in OS.…”
Section: Discussionsupporting
confidence: 92%
“…However, other previous studies confirmed NAC inhibited anti-tumor effect of some chemical agents isolated from the plant, such as britannin, (33) Umbilicaria esculenta, (34) and cryptotanshinone. (35) Consistent with those previous studies, NAC also abolished quercetin-induced NUPR1-depended autophagic cell death in OS cells both in vitro and in vivo. These results also suggested that clinical trials will need to be performed to test if NAC combined with other antioxidants or metabolic modulators are effective in OS.…”
Section: Discussionsupporting
confidence: 92%
“…CT is one of the tanshinones isolated from Salvia miltiorrhiza Bunge, and now is widely used in several diseases, including high blood pressure, fibrosis, and several malignant tumors. CT was found to induce apoptosis and cell cycle arrest in gastric cancer (GC) cells via reactive oxygen species (ROS)‐mediated MAPK and AKT signaling pathways, and this CT may be a useful compound for the developing anticancer agents for GC . CT also suppressed the proliferation of prostate cancer cells via the inhibition of JNK/STAT3 signaling pathway .…”
Section: Discussionmentioning
confidence: 99%
“…CT has been demonstrated to have anti‐tumor activities in various malignancies, including breast cancer,liver cancer,prostate cancer, and ovarian cancer . CT was found to induced apoptosis and cell cycle arrest in gastric cancer cells via reactive oxygen species (ROS)‐mediated MAPK and AKT signaling pathways . It has been reported that CT was a potent STAT3 inhibitor and inhibited STAT3 Tyr705 phosphorylation effectively in DU145 prostate cancer cells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the NAC that have well‐described antioxidant and radical scavenging activity, it has also been used as an antioxidant in several in many studies (Dodd, Dean, Copolov, Malhi, & Berk, ). Such as, NAC could inhibit the quinalizarin‐induced ROS generation in lung cancer A549 cells and blocked cryptotanshinone‐induced apoptosis in gastric cancer cells (Liu et al, ; Meng et al, ). In this study, to determine the relationship of NTDMNQ‐induced apoptosis and ROS, the NAC was used to pretreat the AGS cells.…”
Section: Discussionmentioning
confidence: 99%